The Impact of Heavy Metal Accumulation on Some Physiological Parameters in Silphium perfoliatum L. Plants Grown in Hydroponic Systems - Radu Liviu Sumalan; Vlad Nescu; Adina Berbecea; Renata Maria Sumalan; Manuela Crisan; Petru Negrea; Sorin Ciulca (Plants, 2023)
Heavy metals like cadmium (Cd), copper (Cu), lead (Pb), and zinc (Zn), resulting from anthropogenic activities, are elements with high persistence in nature, being able to accumulate in soils, water, and plants with significant impact to human and animal health. This study investigates the phytoremediation capacity of Silphium perfoliatum L. as a specific heavy metal hyperaccumulator and the effects of Cu, Zn, Cd, and Pb on some physiological and biochemical indices by growing plants under floating hydroponic systems in nutrient solutions under the presence of heavy metals. One-year-old plants of S. perfoliatum grown for 20 days in Hoagland solution with the addition of (ppm) Cu-400, Zn-1200, Cd-20, Pb-400, and Cu+Zn+Cd+Pb (400/1200/20/400) were investigated with respect to the control. The level of phytoremediation, manifested by the ability of heavy metal absorption and accumulation, was assessed. In addition, the impact of stress on the proline content, photosynthetic pigments, and enzymatic activity, as being key components of metabolism, was determined. The obtained results revealed a good absorption and selective accumulation capacity of S. perfoliatum plants for the studied heavy metals. Therefore, Cu and Zn mainly accumulate in the stems, Cd in the roots and stems, while Pb mainly accumulates in the roots. The proline tended to increase under stress conditions, depending on the pollutant and its concentration, with higher values in leaves and stems under the associated stress of the four metals and individually for Pb and Cd. In addition, the enzymatic activity recorded different values depending on the plant organ, its type, and the metal concentration on its substrate. The obtained results indicate a strong correlation between the metal type, concentration, and the mechanisms of absorption/accumulation of S. perfoliatum species, as well as the specific reactions of metabolic response.